(untitled) (Minerva, 2019)
This paper analyzes the influence of Horace’s carmen 1,23 on a song written by Góngora in 1582 (Corcilla temerosa, or Little Frightened Doe). The study highlights links of Góngora’s poem with other Italian imitations of the Latin ode (Ariosto, Giovanni della Casa). On the other hand, the paper also draws attention to the relevance of the Horatian translations in the Salamanca academic circles of the 16th (fray Luis de León).